Optimized Transverse–Longitudinal Hybrid Construction for Sustainable Design of Welded Steel Plate Girders - Iván Negrin; Moacir Kripka; Víctor Yepes (Advances in Civil Engineering)
I-section girders with different types of steel in the flanges and web (fyf > fyw, respectively) are known as transverse hybrid girders. These have proven to be more economical than their homogeneous counterparts. However, the use of hybrid configurations in the longitudinal direction of the element has yet to be studied. This paper uses optimization techniques to explore the possibility of constructing transverse and longitudinally hybrid (TLH) steel girders. The optimization objective is to minimize the manufacturing cost, including seven activities besides the material cost. The geometrically double symmetric I-girder design subjected to a uniform transverse load is performed using Eurocode 3 specifications. Nine case studies are implemented, varying the element span (L) and the applied load. The results show that establishing various configurations along the length of the element is beneficial. The optimum number of transition points is six, meaning the girder will have four configurations, i.e., one central and three others symmetrically distributed toward each half of the element. The optimum position for the first transition would be at 0.24∗(L/2), the second at 0.40∗(L/2), and the third at 0.60∗(L/2). The optimum extreme configuration is usually homogeneous (fyf = fyw = 235 MPa). The others increase the steel quality in the plates, maintaining hybrid arrangements to reach the central one that usually remains with S700 steel for the flanges and S355 for the web. The study shows that TLH configurations are more effective for elements with larger spans. By applying the formulated design recommendations in a different case study, the manufacturing cost dropped by over 50% compared to the traditionally designed element and by more than 10% relative to the optimized element with a homogeneous configuration. The study’s limitations and encouraging results suggest future lines of research in this area.